Screening of α-Glucosidase Inhibitors in Cyclocarya paliurus Extracts Based on Affinity Ultrafiltration-Liquid Chromatography-Mass Spectrometry Combined with Correlation Analysis - Zude CHEN; Boji MA; Yan XIAO; Rengeng SHU; Bingtao LI; Li JIANG; Guoliang XU; Qiyun ZHANG (Shipin gongye ke-ji)
Objective: To rapidly screen α-glucosidase inhibitors in the extract of Cyclocarya paliurus, the affinity ultrafiltration-liquid chromatography-mass spectrometry technique combined with correlation analysis were used to explore the relationship between the active components and enzyme inhibitory activities. Methods: The change matrix (X matrix) of the same chemical component in ethanol elutes of different concentrations of Cyclocarya paliurus was established by using macroporous adsorption resin. The inhibitory effects of α-glucosidase at each ethanol elution site in vitro were analyzed and the effect matrix (Y matrix) was constructed. Potential active ingredients were predicted by partial least squares regression (PLS) to be compared with compounds screened by affinity ultrafiltration (AUF) and validated by molecular docking. Results: The IC50 value of 50% ethanol extract of Cyclocarya paliurus was 14.8 μg/mL, while the IC50 values of the ethanol elution of concentrations ranging from 10% to 80% after adsorption on microporous resin ranged from 5.4 μg/mL to 204.1 μg/mL. Through AUF combined with correlation analysis, a total of 10 potential active components of Cyclocarya paliurus were identified in both positive and negative ion modes. Among them, 8 triterpenoids and 2 flavonoids were identified. Further molecular docking results showed that the binding energy of the 10 active ingredients to α-glucosidase was less than −7.0 kcal·mol−1, and the binding energy of ursolic acid lactone was the lowest (−10.0 kcal·mol−1). Conclusion: The combination of AUF with correlation analysis can quickly and effectively screen potential α-glucosidase inhibitors from Cyclocarya paliurus extracts. The results of this study can lay a foundation for further identifying the active ingredients of Cyclocarya paliurus and provide a basis for further research on the quality control of active ingredients and the development of functional food.